Altitude and slope aspects as the key factors affecting the change of C:N:P stoichiometry in the leaf-litter-soil system of alpine timberline ecotones of the Sygera Mountains in Southeast Tibet, China - He, Peng; Lu, Jie; Ren, Yihua; Li, Jiangrong; Hou, Lei; Deng, Xiangsheng; Gao, Tan; Cheng, Fei (Geoderma Regional, 2023)
Understanding the altitudinal distribution patterns of ecological stoichiometry is essential for understanding biogeochemical processes in mountainous forests. However, the changes in ecological stoichiometry throughout the leaf-litter-soil system on the different slope aspects in mountainous forests ecosystems are not fully understood. To fill these gaps, we examined the altitudinal patterns of C:N:P stoichiometry in the leaf-litter-soil system and nutrient resorption of dominant tree species in the alpine timberline ecotones on the sunny and shady slopes of the Sygera Mountains in Southeast Tibet, China. Three timberline plants were selected: Sabina saltuaria (S. saltuaria), Abies georgei (A. georgei) and Rhododendron aganniphum (R. aganniphum). The C, N, and P contents and C:N:P stoichiometry of R. aganniphum in the leaf and foliar litter varied widely along the altitudes, and those of soil showed similar trends. The leaf C:N of R. aganniphum, soil C, and soil C:N on the sunny slope increased with increasing altitudes. Furthermore, the N and P contents in the leaf and foliar litter of timberline plants on the shady slope were significantly higher than those on the sunny slope, whereas the C, C:N, C:P, and N:P ratios in the leaf and foliar litter exhibited the opposite trend. R. aganniphum had the highest nitrogen resorption efficiency (NRE) and phosphorus resorption efficiency (PRE), whereas A. georgei had the lowest. The PRE of R. aganniphum increased with increasing altitudes, which may be driven by the soil C:N ratio. According to leaf N:P ratios and the relative resorption hypothesis, the leaf N:P ratio was 5.55, 8.70 and 2.86 corresponding to NRE equal to PRE for S. saltuaria, A. georgei and R. aganniphum, respectively. It suggests that the timberline ecotones plants in this study were P-limited, although this limitation may not be responsible for the formation of timberlines in the the Sygera Mountains. Varying degrees of correlations exist between element contents, stoichiometry ratios and nutrient resorption efficiency. Overall, our results revealed that altitude and slope aspects are the key factors affecting the change of C:N:P stoichiometry in the leaf-litter-soil system. •C:N:P stoichiometry of leaf-litter-soil was mainly affected by topography.•R. aganniphum had the highest NRE and PRE, while A. georgei had the lowest.•PRE of R. aganniphum increased with altitudes, which might be driven by soil C:N.•The timberline ecotones plants in this study were generally P-limited.